Research on Coal Mechanical Properties Based on True Triaxial Loading and Unloading Experiment. (16th March 2021) - Peng, Yanyan; Deng, Haoxiang; Xing, Minghong; Guo, Pengfei; Zhu, Chun
Abstract : To study the safety issues caused by coal mine excavation, self-developed simulation of earth interior atmosphere and sound test system was used to perform true triaxial loading and unloading tests of coal. An acoustic emission detection system was used to record the damage evolution trend of coal under different intermediate principal stress states. The experimental results show that in the true triaxial unloading test, as the intermediate principal stress increases, the failure state of coal changes from shear failure to partial shear tension failure, finally leading to overall yield failure. In the stress-strain curves, with the increase in intermediate principal stress, the strain in the direction of intermediate principal stress gradually changes from compression to expansion, and typical expansion occurs. The Mogi–Coulomb strength criterion better reflects the strength failure characteristics of coal during unloading. The stress-acoustic emission diagrams show that the increase in intermediate principal stress causes the internal cracks of the coal to grow unsteadily and exponentially, and the increase in intermediate principal stress makes the coal lose its ability to continue to bear the load. Studying the influence of the intermediate principal stress on the mechanical properties of coal has practical significance for coal mine safety production.